Secretion in yeast: in vitro analysis of the sec53 mutant. - Hibbs, A R (1988)
Of central importance to studying protein translocation via a combined genetic and biochemical approach is the in vitro analysis of yeast conditionally-lethal secretory mutants. Analysis of sec53 presented an opportunity not only to see if mutants could be examined in recently developed yeast in vitro translocation systems, but also to characterize further the nature of this mutant originally postulated to be defective in protein translocation. Membranes from sec53 were capable of translocating and glycosylating nascent prepro-alpha-factor in vitro in both sec53 and wild-type lysates at temperatures that were non-permissive for growth of the mutant cells. These results suggested that the Sec53 protein does not function directly in the translocation and glycosylation of prepro-alpha-factor. To examine this point further, we isolated membranes from sec53 cells that had been grown at the non-permissive temperature prior to disruption. In such cases, regardless of assay temperature, membranes from sec53 cells efficiently translocated but failed to glycosylate prepro-alpha-factor in vitro. The in vitro phenotype of sec53 could be mimicked by isolating rough microsomes from wild-type cells that had been grown for 1 h in the presence of tunicamycin. Together, these results demonstrate that sec53 is not defective in translocation, rather in assembly of the dolichol-oligosaccharide substrate needed for N-linked glycosylation.